2006
DOI: 10.1620/tjem.208.49
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association between a Newly Identified Promoter Polymorphism (-1702G > A) of the Leukotriene C4 Synthase Gene and Aspirin-Intolerant Asthma in a Korean Population

Abstract: Aspirin-intolerant asthma (AIA) is a distinct clinical syndrome that refers to the development of bronchoconstriction in asthmatic individuals following the ingestion of aspirin and other nonsteroidal anti-inflammatory drugs (NSAIDs). It is widely recognized that increased cysteinyl leukotriene (cysLT) biosynthesis is associated with the development and progression of AIA. Leukotriene C4 synthase (LTC4S) is the terminal enzyme in cysLT production and is a strong candidate gene in the pathogenesis of aspirin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Although no data are yet available in children, genetic factors apparently involved in similar reactions in adults from South East Asia have been found to be different than in Caucasian populations studied [19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 92%
“…Although no data are yet available in children, genetic factors apparently involved in similar reactions in adults from South East Asia have been found to be different than in Caucasian populations studied [19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 92%
“…(122,125). In Asian populations, aspirin sensitive asthma patients showed a higher frequency of the C allele in one study (270 individuals, p = 0.042), but this could not be reproduced elsewhere (109,120). Discordances in the results are seen among the same ethnic populations (Asian and Caucasian).…”
Section: Lta4h and Ltc4smentioning
confidence: 91%
“…Approximately half of the published genetic studies found the C allele associated with asthma, asthma severity or aspirin intolerance (105,(115)(116)(117)(118). The other studies, including two also investigating another promoter polymorphism ()1072 G>A) did not detect an association with those same phenotypes (109,(119)(120)(121)(122)(123)(124)(125)) (see Table 3). Interest- (113) 3¢UTR, 3¢ untranslated region; 5¢UTR, 5¢ untranslated region; A, asthma; AD, atopic dermatitis; AIA, aspirin intolerant asthma; AICU, aspirin intolerant chronic urticaria; AL, allergic; ALOX5, 5-lipoxygenase; ALOX5AP, 5-lipoxygenase activating protein; AR, allergic rhinitis; ATA, aspirin tolerant asthma; C, controls (population); C, coding region (location); I, intronic; LTA4H, leukotriene A4 hydrolase; LTC4S, leukotriene C4 synthase; NAL, nonallergic; P, promoter; SA, severe asthma; SNP, single nucleotide polymorphism.…”
Section: Lta4h and Ltc4smentioning
confidence: 99%
“…However, these findings were not replicated in Japanese, American, and Korean populations [20][21][22]. Recently, three SNPs (À634C>T, À475A>C, and À336A>G) in the promoter region of CysLTR1 were identified and the mutant variants of these three SNPs were associated with the AERD phenotype [12] and increased expression of CysLTR1 in peripheral mononuclear cells in the Korean population [22]. In addition, a study performed in the Korean population showed that the frequencies of the rare alleles for À819T>G, 2078C>T, 2534A>G of CysLTR2 were significantly higher in the AERD group [13], which were also noted in Caucasian [23] and Japanese populations [24].…”
mentioning
confidence: 91%
“…However, these findings were not replicated in Japanese, American, and Korean populations [20][21][22]. Recently, three SNPs (À634C>T, À475A>C, and À336A>G) in the promoter region of CysLTR1 were identified and the mutant variants of these three SNPs were associated with the AERD phenotype [12] and increased expression of CysLTR1 in peripheral mononuclear cells in the Korean population [22].…”
mentioning
confidence: 96%